Irinotecan-Induced Skin Dryness Is Ameliorated By Orally Administered High-Dose Vitamin C In Mice - Nakanishi K (Journal of Experimental Pharmacology, 2019)
Kentaro Nakanishi,1 Kenji Goto,1 Kanako Kondo,1,2 Keiichi Hiramoto,1 Kazuya Ooi1 1Department of Pharmaceutical Science, Suzuka University of Medical Science, Suzuka, Mie 513-8670, Japan; 2Department of Pharmacy, Kuwana City Medical Center, Kuwana, Mie 511-0061, JapanCorrespondence: Kazuya OoiDepartment of Pharmaceutical Science, Suzuka University of Medical Science, Suzuka, Mie 513-8670, JapanEmail zooi@suzuka-u.ac.jpBackground: Vitamin C plays a part in various roles in the human body. In this study, we examined the effect of oral administration of high-dose vitamin C on the skin dryness induced by irinotecan.Methods: To establish the experimental model of irinotecan-induced skin dryness, the drug was intraperitoneally administered for four consecutive days. Simultaneously, oral administration of high-dose vitamin C (4 g/kg) was continued for 4 days.Results: High-dose vitamin C administration ameliorated the skin dryness induced by irinotecan. The expression of caspase-3 and caspase-9, reactive oxygen species, and the number of TUNEL-positive cells increased in the skin of irinotecan-treated mice but were lowered by high-dose vitamin C administration. In contrast, fibroblasts and collagen type I decreased in the skin of the irinotecan-treated mice but was increased by high-dose vitamin C administration.Conclusion: These results suggested that high-dose vitamin C administration can improve the skin dryness induced by irinotecan.Keywords: apoptosis, collagen type I, irinotecan, reactive oxygen species, vitamin C